Obesity Promotes EAE Through IL-6 and CCL-2-Mediated T Cells Infiltration - Ji, Zhe; Wu, Shuai; Xu, Yaru; Qi, Jingjing; Su, Xiaohui; Shen, Lei (Frontiers in Immunology, 2019)
Growing evidence suggests that obesity is associated with the susceptibility and disease severity of multiple sclerosis. The chronic inflammation induced by obesity is believed to contribute to this process. However, the immune mechanisms connecting obesity to the prevalence and pathogenesis of MS are poorly defined. In this study, we show that high fat diet (HFD)-induced obese mice developed an exacerbated EAE as indicated by higher clinical scores and more severe pathological changes in spinal cord than the control mice fed with normal diet (ND), following immunization with myelin oligodendrocyte glycoprotein (MOG) 35–55 peptide. The exacerbation of EAE in HFD mice was associated with enhanced microglial activation and increased expansion of Th1 and Th17 cells. The HFD mice also showed aggravated disease in an adoptive T cell transfer EAE model. Mechanistically, HFD augmented the expression level of IL-6 and CCL-2 both in serum and brain, and blockade of IL-6 and CCL-2 signal ameliorated EAE with reduced T cells infiltration in CNS. Taken together, our results suggest that obesity promotes CNS inflammation in EAE through IL-6 and CCL-2 mediated the inflammatory cells infiltration.